ANALISIS SISTEM INTEGRASI JARINGAN WIFI DENGAN JARINGAN GSM INDOOR PADA LANTAI BASEMENT BALAI SIDANG JAKARTA CONVENTION CENTRE - Surjati, Indra; Chandra, Henry; Prabowo, Agung (Jurnal Teknik Elektro, 2007)
The research studied about designing the integration between Wireless Fidelity(WiFi) and GSM indoor network, followed by the observation of its signal quality andrelated environmental factors. To achieve the research goal, it is mandatory to calculate theEffective Isotropic Radiated Power (EIRP) and the Signal Strength (SS) for GSM network orReceived Signal Strength Indication (RSSI) for Wireless Fidelity (WiFi) network. Taking intoconsideration about the GSM and WiFi hardwares specifications, RBS power, Access Pointsand any related enviromental factors; those parameter can be definitely calculated. Theresearch results showed that for GSM indoor network the EIRP 11.9141 dBm and the SignalStrength -70.2759 dBm; while for WiFi network the EIRP 18.7524 dBm and the RSSI -37.3376 dBm with to System Operating Margin is 30.6624 dB. Furthermore it can be statedthat for obtainning the improved output signal strength as implementation of integratingboth network system, it advisable to add Multi Band Combiner altogethet with booster at theGSM network side.Keywords: WiFi, GSM Indoor, Effective Isotropic Radiated Power (EIRP), Received SignalStrength Indication (RSSI).